Warrior Gods and Otherworldly Lands: Daoist Icons and Practices in Late Chosŏn Korea - Maya Stiller (Religions, 2022)
This article brings Chosŏn dynasty (1392–1910) Korea into the discussion about the various roles of Daoism in East Asian cultures in which it has, unfortunately, all too often been absent. Based primarily on art-historical methodology and literary analysis, the article offers an overview of the many sorts of sources and materials that determine the perspectives we have of Daoism-related beliefs and concepts during the late Chosŏn. In contrast to earlier interpretations of Daoist practices as exclusively expressing a desire to retreat from public life, the materials discussed in this article advance a more subtle understanding of the pervasiveness of Daoism in late Chosŏn society, ranging from Daoist divination texts and rituals at religious shrines to the construction of artificial mountains for theater performances and the establishment of government office gardens that served as conduits for spiritual rejuvenation and display of cultural cachet.